Temporal trends in the epidemiology of childhood severe visual impairment and blindness in the UK. Issue 5 (23rd December 2021) - Teoh, Lucinda J; Solebo, Ameenat Lola; Rahi, Jugnoo S
Abstract : Background/aims: Understanding temporal trends in childhood visual disability is necessary for planning and evaluating clinical services and health policies. We investigate the changing epidemiology of severe visual impairment (SVI) and blindness (BL) in children in the UK in the 21st century. Methods: Comparative analysis of two national population-based epidemiological studies of incident childhood SVI/BL (ICD-10 definition; visual acuity worse than 1.0 LogMAR in the better eye). We carry out comparative analysis of studies conducted in 2000 and 2015 using identical methods. Results: Overall annual and cumulative incidence rates remained broadly stable in 2015 at 0.38 per 10 000 (95% CI 0.34 to 0.41) for 0–15 years old and 5.65 per 10 000 (5.16 to 6.18) by 16 years, respectively, and with annual incidence in infancy (3.52 per 10 000, 3.13 to 3.97) remaining considerably higher than any other age. Mortality among children diagnosed in infancy declined (from 61.4 to 25.6 per 1000), despite an increase (from 77% to 84%, p=0.037) in the overall proportion with significant non-ophthalmic impairments/disorders. The relative contribution of all the main groups of disorders increased over time, most notably cerebral visual impairment (from 50% to 61%). Aetiological factors operating prenatally continued to predominate, with an increased relative contribution of hereditary conditions in all children (from 35% to 57%,  p<0.001). The substantially elevated rates for any ethnic minority group and those born preterm were unchanged, with amplification of increased rates associated with low birth weight. Conclusion: The changing landscape of healthcare and increased survival of affected children, is reflected in increasing clinical complexity and heterogeneity of all-cause SVI/BL alongside declining mortality.